Influence of CT dose reduction on AI-driven malignancy estimation of incidental pulmonary nodules - Peters, Alan; Solomon, Justin B.; Stackelberg, Oyunbileg von; Samei, Ehsan; Alsaihati, Njood; Valenzuela Zea, Waldo; Debic, Manuel; Heidt, Christian; Huber, Adrian T.; Christ, Andreas; Heverhagen, Johannes T.; Kauczor, Hans-Ulrich; et al. (European radiology, 2023)
The purpose of this study was to determine the influence of dose reduction on a commercially available lung cancer prediction convolutional neuronal network (LCP-CNN).